Karakteristik Mutasi EGFR pada Pasien Kanker Paru Jenis Adenokarsinoma yang Diterapi dengan Tyrosien Kinase Inhibitor (TKI) di Rumah Sakit Paru Dr. H.A Rotinsulu Bandung - Desi Puspita; Vitri Dwi Astuti; Rina; Edi Sampurno (Sanus Medical Journal, 2022)
This descriptive study describes the proportion of Epidermal Growth Factor Receptor (EGFR) mutations in lung cancer Adenocarcinoma patients at Rumah Sakit Paru (RS Paru) Dr. H. A Rotinsulu Bandung in the range of 2018 to 2020. EGFR mutations were examined using RGQ thera screen technology Real"‘Time Polymerase Chain Reaction from FFPE or cytology smear. There are 44 data point mutations after examining the EGFR mutation. 59% cases were 40"‘60 years old group dan 52 % were female. It was found that in this group 86% patient with single mutation and 16% had doube mutations. EGFR mutations occurred in Exon 21 L858R in 13 cases (30 %), Exon 21 L861Q in 1 case (2%), Exon 19del in 24 cases (55%), double mutation Exon 19 and Exon 20 T790M type in 2 cases (4%), double mutation Exon 19del and Exon 21 in 4 cases (9%).